2021
DOI: 10.1177/17474930211041213
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Patients Treated with Intra-arterial thrombectomy: The optiMAL Blood Pressure control (OPTIMAL-BP) Trial

Abstract: Rationale: Very early stage blood pressure (BP) levels may affect outcome in stroke patients who have successfully undergone recanalization following intra-arterial treatment (IAT), but the optimal target of BP management remains uncertain. Aim: We hypothesized that the clinical outcome after intensive BP-lowering is superior to conventional BP-lowering after successful recanalization by IAT. Sample-size estimates: We aim to randomize 668 patients (334 per arm), 1:1. Methods and design: We initiated a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…We performed a systematic review to estimate the necessary sample size . A total of 3436 articles were identified, of which 9 met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a systematic review to estimate the necessary sample size . A total of 3436 articles were identified, of which 9 met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%
“…This trial was performed at 19 centers throughout South Korea. The protocol is published 16 and provided in Supplement 1 along with the statistical analysis plan in Supplement 2. The trial protocol and consent forms were approved by the institutional review board of each participating hospital, and all patients or their legal representatives provided written informed consent.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Conversely, intraprocedural BP reduction has been related to larger infarct volumes and adverse clinical outcomes, with even a 10% BP drop from baseline being associated with worse functional outcomes. 6,7 Recently completed randomized-controlled clinical trials (RCTs), [8][9][10][11] investigating the safety and efficacy of a stricter BP control among EVT-treated patients compared to standard of care have demonstrated that intensive BP lowering did not reduce the odds of sICH and was associated with adverse 3-month clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, four complete or ongoing trials were introduced. The Korean investigators presented the “Outcome in Patients Treated with Intraarterial thrombectomy: optiMAL Blood Pressure control (OPTIMAL-BP)” trial [ 3 ] and the “Dual antiplatelet Use for extended period taRgeted to AcuTe Ischemic stroke with presumed atherosclerotic OrigiN (DURATION)” study, while the Japanese researchers discussed the “Recovery by Endovascular Salvage for Cerebral Ultra-acute Embolism Japan - Large IscheMIc core Trial (RESCUE-Japan LIMIT)” trial [ 4 ] and the “STroke secondary prevention with catheter ABLation and EDoxaban for patients with non-valvular atrial fibrillation (STABLED)” study [ 5 ]. In addition, presentations on machine learning for stroke subtype classification [ 6 ] and digital stroke therapies [ 7 ] were delivered by Korean speakers, and ring finger protein 213 (RNF213)-related arteriopathy [ 8 ] and multi-lineage differentiating stress enduring (Muse) cell therapy [ 9 ] were presented by Japanese speakers.…”
mentioning
confidence: 99%